PPR IMPLEMENTATION IN MICRO TEACHING COURSE TO IMPROVE STUDENTS’ CONFIDENCE AND COMPASSION - U. Tee, Hannah Elyse; T. Rodrig, Ma. Mercedes (International Journal of Indonesian Education and Teaching (IJIET), 2018)
Apart from technical skills, people must also be educated in social values. This is pertinent in developing well-rounded, socially-aware students. Autism Spectrum Disorder (ASD) is a heterogeneous developmental disability characterized primarily by atypical, repetitive, routinary behavior, as well as impairments in socialization and communication. Despite comprising approximately 1-2% of the world’s population, people with ASD are greatly stigmatized, leading to an overall lower quality of life for them. In order to address this stigmatization, awareness and empathy must be induced in non-autistic, neurotypical people. The rise of serious games or games with a purpose has provided a different avenue for spreading awareness to an audience whose primary interest lies in digital games. Multiple games have been created to spread awareness for issues such as war, cultural discrimination, and mental illness. This study aims to determine whether serious games can also be used to increase autism awareness and lessen the stigma against people with autism. This study makes use of the digital game In Someone Else’s Shoes, which simulates some behaviors of a college student with High-Functioning Autism Spectrum Disorder. For this study, 30 participants were asked to answer a survey on their perceptions on people with autism before playing the game. After which, they answered the same survey again to see if their perceptions had changed, and answered an additional self-report on how the game affected them. While there is minimal change in the perceptions of the players before and after playing the game, the self-report shows that majority of the players expressed feeling more informed about autism, showing a positive cognitive response. However, players reported that the game was not as effective at eliciting an emotional response from them, though they still expressed a willingness to aid someone with autism.DOI: https://doi.org/10.24071/ijiet.2018.020103